GEOPHYSICAL RESEARCH FOR GEOLOGICAL STRUCTURE DETERMINATION IN THE REGION OF SOUTH MESOGHEIA (ATTICA) - Alexopoulos, J.D.; Dilalos, S. (Bulletin of the Geological Society of Greece, 2010)
During the last years the broader area of Koropi (Mesogheia-Greece), has faced rapidly increasing problems concerning irrigation and watering of the town, due to the brackish water in the water supply boreholes. Our main target is to determinate the subsurface geological structure of the study area, located NE of the Koropi city, where alterations of schists and carbonates, from three different post-alpine units, mainly appear and relate it with the groundwater flow paths. The dominant geological outcrops of the area are the Athenian Schist (Laurion-Attica Unit), the dolomitic marbles (Vari-Kirou Pira Unit) and the Lower Marble (Hymittos Unit). A geophysical research was carried out in the area mainly based on the geoelectrical methodology, including by executing fifteen Vertical Electrical Soundings and one Electrical Resistivity Tomography. The interpretation results of the geophysical data have been evaluated and combined with “in-situ” resistivity measurements and calibrated with cores coming from drilled boreholes revealing the area. Through this combining process important elements of the local geological subsurface structure have been determined, as the formation of the dolomitic marbles (massive or karstified) was found tilting southwards beneath the Athenian Schist. From a hydrogeological point of view, this alone adds a significant parameter to the subsurface geological structure which is highly related to the groundwater flow that is responsible for many problems and could be used for solving many others.